Collocational Pattern of Adjectives in The Lexical Field of Beauty : A Corpus-Based Study - Ni Putu Diahtari Ariestiawati; Gede Primahadi Wijaya Rajeg; I Nyoman Tri Ediwan (FKIP, Universitas Palangka Raya, 2023)
This study investigated the usage differences and similarities of adjectives namely beautiful, pretty, and gorgeous through collocational patterns of nouns they modify in the [adjective + noun] construction (Benson, Benson, and Ilson 1986). The collocational patterns were analysed in terms of the semantic field categories using the Concepticon catalogue and of the noun types of the collocates using theory by (Wren and Martin 2000). The data sources were taken from the Corpus of Contemporary American English (COCA) and the analyses adopted the mix-method approach. In terms of their frequencies, beautiful is the most frequent (hence more common) than pretty and gorgeous. beautiful conveys a meaning of aesthetically pleasing, feelings, or thoughts. The highest semantic field categories for the collocate types of beautiful were “Basic action and Technology” and “Speech and Language”. pretty produced more varied noun collocation than beautiful. pretty conveys meaning of fine looking without being truly beautiful or handsome. “Emotions and Values” and “Possession” were the highest semantic categories of collocates for pretty. Finally, gorgeous attaches more to something that is extremely stunning. The category “Kinship” was very dominant for gorgeous. To conclude, collocational pattern and semantic field can expose the different usage of the three semantically similar adjectives.